Strategi Kepala Sekolah Dalam Meningkatkan Prestasi Siswa Melalui Program Tahfidz Alquran Dan Hadits - Mariyam, Ita Nur; Hamzah, Akhmad Fauzi (PT. Cahya Edupreneur Indonesia, 2025)
This study aims to reveal a principal's strategy in improving student achievement through the Quran and hadith memorization program at SMP Plus Fityani Pujon, Malang. The background of the research is based on the low level of education of Indonesian society and the importance of religious value-based education as an effort to shape student character and achievement. The research used a qualitative approach with descriptive methods, involving interview, observation, and documentation techniques to explore in depth the planning, implementation, and implementation of the principal's strategy. The results showed that the principal plays a central role in designing, implementing, and evaluating the tahfidz program using the Ummi method for the Quran and the drill method for hadith, and is supported by the fullday school system and routine religious activities. The strategies implemented include daily intensive learning, assistance in dormitories and homes, and periodic evaluation through various activities such as halqoh, assessment, tasmi', and public testing. The impact of this strategy has proven to be effective, with more than 50% of students achieving the target of memorizing at least 5 juz of the Quran and 42 hadith, even some students are able to memorize up to 30 juz. This study recommends the strategy of the principal of SMP Plus Fityani as a model in improving students' academic and spiritual achievements through the integration of the Quran and hadith memorization program in an Islamic school-based environment.